Avaliação do triticale (X triticosecale wittimack) para silagem - Jobim, Clóves Cabreira; Reis, Ricardo Andrade [UNESP]; Rosa, Beneval; De Andrade Rodrigues, Luis Roberto [UNESP] (My University, 1996)
Silages from three cultivars of triticale (X Triticosecale wittimack) were evaluated at the UNESP, Jaboticabal, Brazil. The cultivars FCA VJ-CB-01, FCA VJ-CB-02, and FCA VJ-CB-03 were harvested for silage in three growing stages of maturity; beginning of flowering, (S1), milk stage (S2), and dough stages (S3). Data were analyzed by randomized complete block with three replications. The DM (%) values increased while the CP (%DM) and buffering capacity (me HCl/100 g DM) decreased with plant development. Silages of plants harvested at S3 stage had higher pH and N-NH3 values compared to the S1 and S2 silages. The soluble carbohydrates contents (%DM) were higher at the S2 stage (16.9%) and were not different at the S1 (8.7%) and S3 (9.2%) stages. The crude energy contents (Kcal/kg MS) increased while the ADF, NDF, cellulose, and hemicellulose (DM%) decreased due to the presence of dough grains. This was not observed with the lignin contents. The IVDMD values were 66.3, 60.1 and 58.9%, for plants harvested at the S1, S2, and S3 stages, respectively. The results showed that there was no difference among for chemical composition, crude energy, and for IVDMD.
Evaluation of triticale (X triticosecale wittimack) for silage
Keywords: Chemical composition; Growing stage; Quality; Silage; X triticosecale